Islamic Education In The Time of Kalifah Umar Bin Khattab and Its Relevance To Education In The Contemporary Era - Dahlan, Zaini; Lingga, Salman Al-Farisi; Assingkily, Muhammad Shaleh (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Islamic education during the Caliphate of Umar bin Khattab displayed significant achievements, in the form of the deployment of scholars to areas of expansion that were won by Muslim troops. This study aims to describe Islamic education during the caliph Umar bin Khattab. The focus of the discussion is a descriptive analysis of Islamic education during the caliph Umar and its impact if implemented in contemporary Islamic educational institutions. For this reason, research data collection uses observation, interviews and documentation studies. Sources of data and study analysis materials use scientific literature in the form of articles, books, seminar proceedings, and final assignments (thesis, thesis, or dissertation). To check the validity of the data, the researcher cross-checked the findings with the research material. The results of this study concluded that Islamic education at the time of Caliph Umar had achieved an extraordinary civilization by producing scholars who were qualified in various fields of knowledge. This is inseparable from the efforts of the caliph Umar who implemented equality-based education for all people, free education for all people, and strengthened the role of the state in supervising, maintaining, supporting, and even financing anyone who studies. On the other hand, even prisoners of war in an effort to expand Islamic territory will not be killed or imprisoned if they are willing to become teaching staff for the Muslims.